‘I Know We’ve Got Someone in the School I Can Trust’: Students’ Attitudes Towards School Counselling Services in Slovenian Schools - Šarić, Marjeta; Jeznik, Katja; Mažgon, Jasna; Gregorčič Mrvar, Petra (Pedagogika, 2020)
This article examines the role of the school counselling service as a protective factor in adolescents’ lives. School counsellors provide adolescents with information, emotional support, and counselling, and for many adolescents, they are the only source of support outside the family. The findings of a study conducted among 1,363 primary school students and 306 secondary school students from Slovenia are presented. The data showed that the students regard school counsellors favourably, and they generally have a high degree of trust in them.